If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -11x = -2(x + -4) + 4(-9x + -11) Combine like terms: 9x + -11x = -2x -2x = -2(x + -4) + 4(-9x + -11) Reorder the terms: -2x = -2(-4 + x) + 4(-9x + -11) -2x = (-4 * -2 + x * -2) + 4(-9x + -11) -2x = (8 + -2x) + 4(-9x + -11) Reorder the terms: -2x = 8 + -2x + 4(-11 + -9x) -2x = 8 + -2x + (-11 * 4 + -9x * 4) -2x = 8 + -2x + (-44 + -36x) Reorder the terms: -2x = 8 + -44 + -2x + -36x Combine like terms: 8 + -44 = -36 -2x = -36 + -2x + -36x Combine like terms: -2x + -36x = -38x -2x = -36 + -38x Solving -2x = -36 + -38x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '38x' to each side of the equation. -2x + 38x = -36 + -38x + 38x Combine like terms: -2x + 38x = 36x 36x = -36 + -38x + 38x Combine like terms: -38x + 38x = 0 36x = -36 + 0 36x = -36 Divide each side by '36'. x = -1 Simplifying x = -1
| 2b+4=-18-9 | | 6c+4+8= | | 2y-2-2y-7=6y+3-9 | | -7x+32=-6x+8(4-5x) | | (x-3)-25=0 | | -6y=3 | | 3(2x-7)=7x-20 | | 10=z-4 | | .04x+.05y=140 | | 7-3x7/8 | | 0.8x+0.2y=1500 | | -48=-6y-7 | | 3(3n)-3(5)+4n=6+3(n)-2(4n)+5(4) | | 3x+8y=1 | | -8y+-y-5y= | | 5+2x=-5x | | b-8+6b=23 | | 5x-2+1.3(9x-33)=5 | | 11/17=13/u | | 3g+3(2-g)=-4(g+1) | | y=8x-4/5 | | P-1=5+5p-8 | | -5-10u+-7u= | | 3x^3-8x^2-x+10=0 | | 5x-(2x-6)=12 | | x+2=15x | | 8g+3(2-g)=-4(g-1) | | 4x-1/3y=5 | | 4(2y-1)-6y=8 | | 42/14=p+15/p-5 | | F(X)=3x^2-5x-8 | | 2x+90=35 |